Modern possibilities for treating acute rhinosinusitis using herbal medications - Valery M. Svistushkin; Liliya V. Selezneva; Mikhail V. Svistushkin; Gaya V. Lebedeva; Igor A. Zinchenko (Consilium Medicum)
Aspects of the clinical use of herbal preparations for acute rhinosinusitis (ARS) are considered, in the pathogenesis of which swelling of the mucous membrane of the nasal cavity and paranasal sinuses plays a key role. The irrational use of antibacterial drugs for the treatment of uncomplicated ARS has led to the emergence of antibiotic-resistant strains of bacteria and the need to search for alternative treatment methods. Convincing evidence is presented for the need to use herbal medicines in both complex and monotherapy of ARS of viral and bacterial origin. This review assessed the quality of the evidence for the use of herbal medicine for acute rhinosinusitis to determine its position among other treatments and future directions for research. Clinical studies of the effectiveness of the drug Sinupret extract are presented, the use of which promotes the outflow of exudate from the paranasal sinuses and upper respiratory tract, preventing the development of complications.